Pengaruh Promosi, Lokasi, dan Kualitas Pelayanan terhadap Keputusan Pembelian : Studi pada Konsumen Kalula.Outfit di Jakarta Barat - Syiffa Azzahra; Elizabeth Elizabeth (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The large number of fashion brands in Indonesia opens up opportunities for competition to create purchasing decisions. In the competitive world of fashion clothing, product quality and differentiation are the main keys in influencing consumer purchasing decisions. Kalula.Outfit must face pressure from GBS_Clothes and Maryam Outlet which offer more exclusive and innovative designs. This study aims to determine the Promotion, Location, and Service Quality Partially and Simultaneously on Purchasing Decisions of Kalula.Outfit consumers in West Jakarta. This type of research is quantitative. The technique for determining the population uses non-probability sampling. The population in this study is not known with certainty. Sampling uses the lemeshow formula. The sample used in this study was 97 respondents, with the accidental sampling questionnaire distribution method. In this study, the data were analyzed using the SPSS version 25 program and Microsoft Excel 2019. The results show that Promotion, Location, and Service Quality partially and simultaneously influence purchasing decisions.